Corporatism and Fascism: The Corporatist Wave in Europe - Pinto, António Costa (2017)
This book is the first conceptual and comparative empirical work on the relation between corporatism and dictatorships, bringing both fields under a joint conceptual umbrella. It operationalizes the concepts of social and political corporatism, diffusion and critical junctures and their particular application to the study of Fascist-Era dictatorships. The book’s carefully constructed balance between theory and case studies offers an important contribution to the study of dictatorships and corporatism.